Mahram dan Transformasi Zaman: Sebuah Anallsis Fiqhiyyah dan Keadilan Gender - Tahir, Masnun (Musawa Jurnal Studi Gender dan Islam, 2010)
"No ... of a man and a woman except if their mahram, and no travellingfor a woman except with her mahram"This long sentence is now decoratingmany public space in Aceh, including on ther tree trunks in the city gardens where young unmarried couples might be interested in enjoying. This propaganda is based on the province Qanun (regulation) No 14/2003 about prohibition of kludwat (...). This paper will not deal with the Qanun per-se, rather with the underlying arguments used by the proponents of the articulation of the Qanun by local intellectuals. My discussion to the issue begins with the examination of the social context within which the hadits aboui mahram is conceptualized, then followed by a deep analysis on the formulation of Fiqh (Islamic law) as well as gender analysis on the impact of mahram concept to women's mobility. At the end present my recommendation in applying transformative understanding on the mahram concept.